Methods Of Guidance And Counceling Section In Building Character Of Six Grade Students Of Arrisalah Islamic International College Slahung Ponorogo East Java - Dwi Nurcahyaningtias, Novia; Mutaqi, Ibnul (Fakultas Tarbiyah dan Ilmu Keguruan UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
The students of Six Grade are the highest-class students at Arrisalah Islamic International College, however, some of them are still not noble. As the results of the author's interviews with several students of class VI, they realize that their morals are still not good. If this reality continues to occur, then the next generation will be even more damaged. Moreover, Six Grade students will become teachers because they are charged with serving in Islamic educational institutions after graduation. So it is necessary to have methods of fostering morals and the best methods can be found in them. The purpose of this study was to find out (1) the methods of assisting students in nurturing the morals of students of class VI Kulliyyatu-l-Mu'allimin Al-Islamiyyah Arrisalah Islamic International College (2) the obstacles faced by assistants caring for students in developing the morals of students of class VI Kulliyyatu -l-Mu'allimin Al-Islamiyyah Arrisalah Islamic International College. This research uses a qualitative approach and field research type of research. The data collection process uses in-depth interviews, non-participatory observation and documentation. While the data analysis technique used is the flow technique from Miles and Huberman which includes three steps, namely data collection, data presentation, and conclusions. From the analysis of the data it was found (a) methods of assisting the upbringing of students in fostering the morals of class VI students, including: (1) the method of religious awareness by praying in congregation (2) the method of giving stories of the Prophet (3) the exemplary method (4) the method of habituation (5) methods of giving rewards and punishments. And (b) the obstacles faced by the santri parenting assistant in fostering the morals of Six Grade students are (1) the lack of religious awareness of some Six Grade students of the importance of having noble morals (2) the abundance of information and easy access to it (3) the cultural diversity of students (heterogeneity). The author hopes that the assistants caring for the students of Arrisalah Islamic International College will always be consistent in carrying out their duties and programs in fostering the morals of Six Grade students so that their morals become good and noble.